RENCANA MUTU KONTRAK Studi Kasus Pekerjaan Perencanaan pada Kegiatan Participatory Irrigation Sector Project Kabupaten Banyumas - Chrisna Pudyawardhana (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2007)
Abstract Execution of planning work at activity of Participatory Irrigation Sector Project require to be made by best quality in the form of plan Quality Of Contract Desain (Quality Assurance) as exploiting effort of quality of to be reached by the result design with the best quality is such as those which expected previously and as according to frame of reference work.This study evaluate the document plan quality of contract which have arranged of planner consultant in concerned in course of planning at activity of Participatory Irrigation Sector Project in regency Banyumas, whether have fulfilled the procedure standard going into effect.Such procedure standard cover the target and work target, organizational formation, enlist the personnel, activity schedule, procedure standard/ design, and inspection schedule/ test. Keyword : Plan quality of contract, Consultant, Banyumas.